Dinoflagellate cysts in the surface sediments of the White Sea. - Novichkova, Ekaterina A; Polyakova, Elena I (PANGAEA, 2007)
Dinoflagellate cysts were studied in 42 samples from surface sediments of the White Sea. Total concentration of dinocysts varies from single cysts to 25000 cyst/g of dry sediments, which reflects biological productivity in White Sea waters and regional particular features of sedimentation processes. The highest concentrations are observed in silts; they are related to the regions of propagation of highly productive Barents Sea waters in the White Sea. Generally, spatial distribution of dinocyst species in the surface sediments corresponds to distribution of the major types of water masses in the White Sea. Cysts of relatively warm-water species (Operculodinium centrocarpum, Spiniferites sp.) of North Atlantic origin that dominate in the sediments indicate an intensive intrusion of Barents Sea water masses to the White Sea along with hydrological dwelling conditions in the White Sea favorable for development of these species during their vegetation period. The cold-water dinocyst assemblage (Islandinium minutum, Polykrikos sp.) is rather strictly confined to inner parts of shallow-water bays, firstly, those adjacent to the Onega and Severnaya Dvina river mouths.
Concentrations of dinoflagellate cysts in the surface layer of bottom sediment from the White Sea
Keywords: Archive of Ocean Data; ARCOD; Counting >10 µm fraction; Dinoflagellate cyst per unit mass; Ekolog; Ekolog-2002; Ekolog-2002-10; Ekolog-2002-15; Ekolog-2002-16; Ekolog-2002-3; Ekolog-2002-32; Ekolog-2002-4; Ekolog-2002-40; Ekolog-2002-43; Ekolog-2002-59; Ekolog-2002-62; Ekolog-2002-75; Ekolog-2002-76; Ekolog-2002-77; Ekolog-2002-78; Ekolog-2002-88; Grab; GRAB; IPE-2002; IPE-2002-39; IPE-2002-40; Ivan Petrov; Lithology/composition/facies; MULT; Professor Shtokman; PSh49; PSh49-4684; PSh49-4687; PSh49-4693; PSh49-4694; PSh49-4697; PSh49-4699; PSh49-4700; PSh49-4701; PSh49-4702; PSh49-4703; PSh49-4704; PSh49-4705; PSh49-4706; PSh49-4709; PSh49-4712; PSh49-4713; PSh49-4714; PSh49-4716; PSh49-4717; PSh49-4719; PSh49-4720; PSh49-4721; PSh49-4722; PSh49-4724; PSh49-4728; White Sea